We Don’t Want to Be Sold to Ecuador! A Coup D’état in Costa Rica in the 19th Century - Corella Ovares, Esteban (2019)
The article analyzes the attempted coup d’état carried out by General Manuel Quirós against Juan Rafael Mora, the uprising failed because the general was not able to mobilize enough men to take the San Jose barracks, despite trying to convince the militiamen through the rumor that Mora’s government would force them to fight for Juan José Flores, former president of Ecuador who was in the country at that time. The episode serves as an excuse to examine the means used by members of the elite to mobilize the militiamen who formed most of the armed forces of Costa Rica in the mid-nineteenth century.